2014
DOI: 10.3892/ijmm.2014.1746
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of IKKɛ inhibits inflammation and induces cardiac protection in high-fat diet-induced obesity in mice

Abstract: Immune response and metabolic regulation have been recognized as a central homeostatic mechanism, the dysfunction of which can trigger a cluster of chronic metabolic disorders, particularly obesity, type Ⅱ diabetes and cardio-vascular disease. Serine/threonine kinase IκB kinase (IKK) ε is a multifunctional regulator that participates in immune regulation, cell proliferation and transformation, and oncogenesis. In the present study, we investigated the role of IKKε in cardiovascular disorders using murine model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The membranes were blocked in Tris-buffered saline with Tween 20 (TBST) containing 5% skimmed milk powder for 1 h at room temperature and incubated with various primary antibodies overnight at 4°C. Following incubation with secondary antibodies for 1 h at room temperature, membranes were washed with TBST four times, as previously described (11). Specific proteins were detected using an enhanced chemiluminescence reagent (GE Healthcare, Piscataway, NJ, USA) and captured on Hyperfilm (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were blocked in Tris-buffered saline with Tween 20 (TBST) containing 5% skimmed milk powder for 1 h at room temperature and incubated with various primary antibodies overnight at 4°C. Following incubation with secondary antibodies for 1 h at room temperature, membranes were washed with TBST four times, as previously described (11). Specific proteins were detected using an enhanced chemiluminescence reagent (GE Healthcare, Piscataway, NJ, USA) and captured on Hyperfilm (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Human and Apoe −/− Mice. Previous studies have shown that IKKε plays an important role in regulating cardiovascular disease [6,7]. Therefore, we assessed IKKε expression in abdominal aortic tissues taken from AAA patients and nonaneurysmal controls.…”
Section: Expression Of Ikkε Is Upregulated In Aaa Tissues Frommentioning
confidence: 99%
“…Induced AAA Formation in Apoe-Deficient Mice. Because IKKε activity has been linked to the pathology of inflammatory diseases [5,7], a recent study identified an antiinflammatory drug, amlexanox, as a selective inhibitor of IKKε and an approved small-molecule therapeutic presently used in the clinic to treat aphthous ulcers and in clinical trials for obesity [20]. We assumed that amlexanox administration could efficiently inhibit Ang II-induced AAA in mice; pharmacological inhibition studies were employed using to address this hypothesis.…”
Section: Pharmacological Inhibition Of Ikkε Mitigates Ang Ii-mentioning
confidence: 99%
See 1 more Smart Citation
“…DAPI was used to counterstain the nuclei. Samples were then covered with mounting media (Invitrogen; Thermo Fisher Scientific, Inc.), overlaid with coverslips and examined under a fluorescence microscope (Axio Scope A1; Carl Zeiss AG, Oberkochen, Germany) following the method described in previous studies (19,20). …”
Section: Methodsmentioning
confidence: 99%